Mediation Role of Anxiety Sensitivity on the Relationships between Intolerance of Uncertainty and Fear of COVID-19 - Çelik, Eyüp; Biçener, Eda; Bayın, Ümit; Uğur, Erol (Anales de Psicología / Annals of Psychology, 2022)
The aim of the present study is exploring the mediation role of anxiety sensitivity on the relationships between intolerance of uncertainty and fear of COVID-19. The study was conducted with the relational screening method. The research data were collected online from 302 individuals (Male n = 76, Female n = 226) with Fear of COVID-19 Scale, Anxiety Sensitivity Index-3, Intolerance of Uncertainty Scale. The result of both mediation analysis and bootstrapping analysis (with 5000 bootstrap resamples) showed that the relationship between intolerance of uncertainty and fear of COVID-19 was mediated by anxiety sensitivity. Anxiety sensitivity decreased the effect of intolerance of uncertainty on fear of COVID-19. Moreover, comparing intolerance of uncertainty and anxiety sensitivity in terms of their predictive levels of the fear of COVID-19, it was concluded that anxiety sensitivity predicted the fear of COVID-19 more, and that anxiety sensitivity included the variance of intolerance to uncertainty associated with the fear of COVID-19.